Aplikasi Pupuk Kotoran Hewan (Kohe) Kambing dan Mulsa Serasah Daun Bambu untuk Meningkatkan Pertumbuhan Tanaman Seledri (Apium Graveolens L. var. Secalinum Alef.) - Tia Setiawati; Elah Karimah; Titin Supriatun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
The research aims to determine the optimal dosage of sheep manure and the thickness of the bamboo leaf litter mulch on increase growth of Celery. The research method used by experimental method using group randomize block design, 5 x 3 factorial with 3 replication. The first factor was the adding of sheep manure (P), consist of five levels doses, i.e : without manure (p0); 2,5 g/kg of soil (p1); 5 g/kg of soil (p2)l; 7,5 g/kg of soil (p3) and 10 g/kg of soil (p4). The second factor was bamboo leaf litter mulch (M), consist of three levels, i.e : without mulch (m0); mulch with thickness 2,5 cm (m1); mulch with thickness 5 cm (m2). Parameter observed were the plant height, the number of leaf, the leaf area, the shoot dry weight and the root dry weight. The data obtained was analyzed using Anova and Duncan Multiple Range Test (Î±=5%). Commonly, sheep manure fertilizer dose 5 g/kg of soil (d2) and bamboos leaves litter mulch on the tickness of 5 cm (m2) was the optimum dose for growth of Celery. The result of this research showed interactions beetwen the adding of sheep manure and bamboo leaf litter mulch in increasing the average of the plant growth on the plant height (38 cm) and the number of leaf(34,67 leaves). Keywords : sheep manure, bamboo leaf litter mulch, celery